COLOUR TRADITION & CHALCOLITHIC POTTERY : ताम्राश्मीय पात्र एवं रंग परंपरा - Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2021)
Hindi: "भूतकाल का अध्ययन केवल वर्तमान के माध्यम से ही किया जा सकता है । बीते हुए समय के अध्ययन के लिए वर्तमान वस्तुओं तथा वर्तमान में विद्यमान संस्करणों को भूतकाल के अवशेषों के रूप में लेकर उनसे भूतकाल की घटनाओं के बारे में निष्कर्ष निकाला जाता है। वे तर्क जिनके आधार पर निष्कर्ष निकाले जाते हैं वे वर्तमान वस्तुओं घटनाओं तथा संबंधों के अवलोकन पर आधारित होते हैं"।1 English: The excavation work done in India gives information about the stages of ancient Indian culture and various cultural region and their important characteristics. The materials and pottery found from the excavation of chalcolithic sites in Madhya Pradesh are the direct evidences of tradition of pottery paintings . In Madhya Pradesh the cultural range from the Chalcolithic (Tamrashmiya) period to the early medieval period can be traced to the sites of Kayatha, Ujjain, Nagda, Vidisha, Maheshwar-Nawadatoli, Arawa, etc..The erstwhile pottery here provides a perfect example of the amalgamation of different cultures. The Malwa region of Madhya Pradesh has its own style of personal character tradition, this tradition has been more advanced and elaborate than other eligible traditions.